Answer:
2 i think. :D
Step-by-step explanation:
Step-by-step explanation:
(2a+3b)(4a²-6ab+9b²
(2a+3b){(2a)²-2a×3b+(3b)²}
Because (a³+b³)=(a+b)(a²-ab+b²)
Therefore,
(2a+3b){(2a)²-2a×3b+(3b)²}
=(2a)³+(3b)³
By substituting the values , we get
- (2a)³+(3b)³
- (2×3)³+(3×(-5))³
- 6³+(-15)³
- 216+(-3375)
- 216-3375
- -3159
Answer:
p(4)=4^2-5(4)
P(4)=16-20
P(4)=4
Step-by-step explanation:
9x³-33x²-54x-30 =
3(3x³-11x²-18x-10) =
3(x-5)(3x²+4x+2) so one zero is 5. use the quadratic formula to determine the other 2 roots are a double root at -⅔
I would say the answer is D